KAJIAN KOMPARATIF KITAB UNDANG-UNDANG HUKUM PIDANA PADA KETENTUAN UMUM DALAM SANKSI PIDANA (Solusi, 2023)
Criminal law functions in the context of preventing the occurrence of a criminal act and as a resolution. This research examines the comparison between the old Criminal Code and the latest provisions in Law Number 1 of 2023. The renewal of the Criminal Code in Law Number 1 of 2023 leads to adaptation and harmonization of various legal developments that occur. In substance, there are differences between the old and the new Criminal Code, in that the provisions of the old Criminal Code consist of Main Criminal and Additional Criminal, while in Law Number 1 of 2023 concerning the Criminal Code which consists of: Basic Criminal, Additional Criminal and Special Criminal.